Seroprevalence of Chikungunya Virus in a Rural Community in Brazil. - Rivaldo V Cunha; Karen S Trinta; Camila A Montalbano; Michel V F Sucupira; Maricelia M de Lima; Erenilde Marques; Izilyanne H Romanholi; Julio Croda (Public Library of Science (PLoS), 2017)
BACKGROUND:The emergence of the Chikungunya virus (CHIKV) is currently expanding. In 2015, 38,332 cases of Chikungunya were reported to the Brazilian epidemiological surveillance system. Eighteen months after notification of the first case in the city of Feira de Santana, we conducted the first serosurvey to define the magnitude of transmission in a rural community in Brazil. METHODOLOGY/MAIN FINDINGS:The serosurvey was conducted in a random sample of 450 residences in the Chapada district, located 100 kilometers from Feira de Santana. We administered questionnaires and tested 120 sera from Chapada district residents for CHIKV IgM- and IgG-specific antibodies. An individual with CHIKV infection was defined as any person with CHIKV IgM or IgG antibodies detected in the serum. One Hundred cases of Chikungunya were reported after prolonged rainfall, which reinforced the relationship between the rainfall index and CHIKV transmission. Eighteen months after the start of the outbreak, we identified a seroprevalence of 20% (95% CI, 15.4-35%). CHIKV IgG- and IgM-specific antibodies were detected in 22/120 (18.3%) and 6/120 (5.0%) individuals, respectively. Among seropositive patients, 13/24 (54.2%) reported fever and joint pain over the previous two years (p<0.01). The rate of symptomatic CHIKV infection was 40.7%. CONCLUSIONS/SIGNIFICANCE:We identified a moderate seroprevalence of Chikungunya in the Chapada district, and in half of the confirmed CHIKV infections, patients reported arthralgia and fever over the previous two years.